Stories Make Readers: Enhancing the Use of Fictional Literature With Multilingual Students - Juli-Anna Aerila; Merja Kauppinen (Igi Global, 2022)
Using literature in multilingual and second language classes promotes literacy skills and helps children to adapt to second language instruction. In this chapter, we present the theoretical framework and practical implementations for enhancing the use of literature in multilingual environments employing Stories Make Readers (StoRe)–project as an example. StoRe concept helps to promote the use of fictional literature and to increase the reading materials and reading time at schools and home. An important aim is to offer in multilingual groups reading materials that correspond to the reading abilities and interest of the readers, and to connect different collaborative, child-centered, and multidisciplinary activities in reading. The multilingual line of the StoRe project, called Creating Innovative Approaches to Language Education (IKI), aims to identify and promote innovative models for the use and development of language in education and to create research-based, pedagogical maps that help teachers develop and improve their pedagogical practices.
Handbook of Research on Cultivating Literacy in Diverse and Multilingual Classrooms